Achieving strength-ductility synergy of spark plasma sintered (CoCrNi)94Al3Ti3 medium-entropy alloy via post-sintering in-situ precipitation treatment - Shifeng Luo; Nan Wang; Yan Wang; Xiang Li; Xiaogang Fang; Hongwei Zhou; Jieming Chen; Xinyu Yang; Jiuxing Zhang (Journal of Materials Research and Technology)
The single-phase face-centered cubic medium-entropy alloys (MEAs) normally have coarse grains in as-cast state, which exhibit insufficient strength for engineering applications. Here, a superior tensile strength-ductility synergy in a fine grained (CoCrNi)94Al3Ti3 MEA hardened by nanoscale L12 precipitates was fabricated by spark plasma sintering (SPS) and post-sintering in-situ precipitation treatment. The SPSed MEAs have a fine grain size of ⁓ 5 μm, and a high number density of L12 precipitates form after in-situ annealing within the SPS machine. A high tensile yield strength of 1141 MPa with an adequate elongation to fracture of 25.8% was achieved in (CoCrNi)94Al3Ti3 MEA after annealing at 700 °C for 4 h. Electron backscattered diffraction and transmission electron microscopy characterizations indicate that the superior mechanical properties mainly originate from fine grains and the coherent spherical L12 precipitates. The dislocation slips and stacking faults prevail in all SPSed MEAs during tensile deformation, while extra Lomer-Cottrell locks are observed in annealed MEAs. The deformation twinning is absent in these precipitation-hardened MEAs with a low stacking fault energy, which may be attributed to the fine grains and numerous nanoscale L12 precipitates. This study not only confirms the effectiveness of powder metallurgy when sintering and precipitation are combined in-situ during the SPS cycle, but also provide guidance for the microstructure regulation process and practical applications of SPSed HEAs/MEAs.